Oxidation Adsorptive Desulfurization of Jet Fuel Using Mesoporous Sieve Loaded with TiO2. Issue 12 (26th March 2021) - Zhang, Zongwei; Wei, Keheng; Li, Chao; Deng, Zhenhong; Chu, Feixue
Abstract: Herein we report a simple process involving catalytic adsorptive desulfurization (CADS) of model jet fuel under mild conditions with H2 O2 using TiO2 loaded on MCM‐41, SBA‐15, or multi‐walled carbon nanotubes (MWCNTs) prepared by ultrasonic assisted initial wetting impregnation. The removal of dibenzothiophene (DBT) was investigated in terms of the oxygen/sulfur ratio, temperature, loading capacity, competitive components and adsorption kinetics. The adsorption capacity and adsorption strength of TiO2 /MCM‐41 were higher than those of TiO2 /SBA‐15, which are related to the higher SBET of MCM‐41, or the presence of numerous silanol groups. The TiO2 /MWCNTs also showed excellent DBT adsorption capacities. TiO2 /MCM‐41 exhibited better selectivity toward the oxidative‐adsorptive desulfurization of DBT owing to the weak influence of competitive adsorption of aromatics; this was explained by the lack of micropores in the one‐dimensional mesoporous structure. The sample with 1 % TiO2 /MCM‐41 showed a high DBT adsorption capacity and rapid kinetics, and thus proved to be an inexpensive and effective desulfurization adsorbent for producing clean jet fuel. Abstract : Catalytic adsorptive desulfurization (CADS) of dibenzothiophene (DBT) is a promising process to realise ultra‐low‐sulfur clean jet fuel under mild conditions. The sample with 1 % TiO2 /MCM‐41 exhibited a high DBT adsorption capacity, rapid kinetics and a good selectivity toward CADS of DBT with weak influence of competitive adsorption of aromatics, which, along with its low cost, make it an effective desulfurization adsorbent for producing clean jet fuel.